2018
DOI: 10.1111/jfs.12531
|View full text |Cite
|
Sign up to set email alerts
|

Flow rate of depuration system has minimal impact on Vibrio parahaemolyticus decontamination in Pacific oysters (Crassostrea gigas)

Abstract: Vibrio parahaemolyticus infections in the United States have been linked to consumption of raw oysters. Depuration has the potential to reduce contamination in live oysters after harvest. This study investigated the impact of depuration flow rate to reduce V. parahaemolyticus in raw oysters. Pacific oysters (n = 35 per trial) were inoculated with a cocktail of V. parahaemolyticus (10290, 10292, 10293, BE 98‐2029, and 027‐1c1) in freshly prepared artificial seawater (70 L). The inoculated oysters were depurated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Reductions in VV and VP were lower (<3 log MPN/g) when processing took place over 1–3 days compared with longer processing times (Chae et al., 2009). Other studies demonstrated higher reductions of VV and VP (≥3 log MPN/g) in oysters when depuration time was more than 3 days (Ming et al., 2018a; Phuvasate et al., 2012; Phuvasate & Su, 2013; Su et al., 2010; Wang, Yu, et al., 2010).…”
Section: Parameters Affecting the Depuration Of Vibrio From Live Oystersmentioning
confidence: 94%
See 1 more Smart Citation
“…Reductions in VV and VP were lower (<3 log MPN/g) when processing took place over 1–3 days compared with longer processing times (Chae et al., 2009). Other studies demonstrated higher reductions of VV and VP (≥3 log MPN/g) in oysters when depuration time was more than 3 days (Ming et al., 2018a; Phuvasate et al., 2012; Phuvasate & Su, 2013; Su et al., 2010; Wang, Yu, et al., 2010).…”
Section: Parameters Affecting the Depuration Of Vibrio From Live Oystersmentioning
confidence: 94%
“…Another study examined flow rates from 15 to 35 L/min and confirmed higher flow rate might enhance depuration in oysters; however, the authors did confirm that depuration time had a more significant impact in the reduction of VP in Pacific oysters than flow rates (Ming et al., 2018a). The authors also noted depuration flow rate may contribute to modulating an oyster's pumping activity.…”
Section: Parameters Affecting the Depuration Of Vibrio From Live Oystersmentioning
confidence: 99%
“…For this purpose, several studies have conducted an artificial contamination of shellfish product with human pathogenic Vibrio species. The efficiency of the treatment is evaluated in terms of duration of the depuration cycle, water flow rate and density of shellfish per tank to remove the contamination of Vibrio pathogenic species (Barile et al ., 2018; Ming et al ., 2018; Shen et al ., 2019). Other studies investigated the impact of depuration on shellfish products naturally contaminated by Vibrios mainly describing the presence of human pathogenic Vibrio species such as V. cholerae 01, V. parahaemolyticus and V. vulnificus (Croci et al ., 2002; Sferlazzo et al ., 2018; Tokarskyy et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%